2012
DOI: 10.1111/j.1460-9568.2012.08071.x
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine and gamma band synchrony in schizophrenia – insights from computational and empirical studies

Abstract: Dopamine modulates cortical circuit activity, in part, through its actions on GABAergic interneurons, including increasing the excitability of fast-spiking interneurons. Though such effects have been demonstrated in single cells, there are no studies that examine how such mechanisms may lead to the effects of dopamine at a neural network level. With this motivation, we investigated the effects of dopamine on synchronization in a simulated neural network, composed of excitatory and fast-spiking inhibitory Wang-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
49
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(53 citation statements)
references
References 60 publications
(63 reference statements)
4
49
0
Order By: Relevance
“…In a recent empirical and modeling study, amphetamine administration induced gamma decreases and increases in healthy and patient participants, respectively [80], changes replicated in a PFC model [80]. In a hippocampal network model [81], dopamine had the opposite effect, reducing stimulus-induced gamma activity in “putatively schizophrenic” parameter regimes and increasing it in others.…”
Section: Cellular Molecular and Circuit Level Changes Alter Rhythmsmentioning
confidence: 98%
“…In a recent empirical and modeling study, amphetamine administration induced gamma decreases and increases in healthy and patient participants, respectively [80], changes replicated in a PFC model [80]. In a hippocampal network model [81], dopamine had the opposite effect, reducing stimulus-induced gamma activity in “putatively schizophrenic” parameter regimes and increasing it in others.…”
Section: Cellular Molecular and Circuit Level Changes Alter Rhythmsmentioning
confidence: 98%
“…A MEG study of mental arithmetic found lower induced left frontal gamma activity at low frequency sub-bands (30–45 Hz), but higher right frontal and fronto-temporal activity at higher frequency sub-bands (46–71 Hz) (46), suggesting disturbances of specific sub-bands of the gamma range. Although not probing prefrontal circuits specifically, ASSR paradigms provide convergent support for such frequency specificity, consistently identifying 40 Hz deficits in schizophrenia (27;29;30;47;48), including a study that sampled sub-bands from the gamma range, and found deficits in the 30–45 Hz range for phase-locking factor and total power in patients (30). Another study combined transcranial magnetic stimulation (TMS) with EEG to probe for gamma deficits in schizophrenia; relative to healthy controls the natural frequency responses in the frontal regions of the schizophrenia subjects were lower in the gamma range (31).…”
Section: Frontal Cortical Gamma Oscillation Disturbances In Schizophrmentioning
confidence: 99%
“…For example, computational studies have highlighted the important role of PV cell excitability in modulating network gamma oscillations (29;68;135), including demonstrations of cell type-specific effects (135). In addition, the development of novel experimental methods in the form of optogenetics (19) and DREADD (Designer Receptors Exclusively Activated by Designer Drugs) approaches (136) have provided the basis for explicit cell type-specific empirical investigations of the effects of excitatory-inhibitory balance shifts on gamma oscillations.…”
Section: Cortical Parvalbumin Neurons In Schizophreniamentioning
confidence: 99%
“…However, the exact mechanism through which DA leads to such non-monotonic modulation of network activity needs further investigation. Our recent work suggests that DA's modulation of potassium currents in the fast-spiking interneurons could be a potential mechanism underlying this inverted-U relationship [2]. Here we propose that another potential mechanism could contribute in the form of interactions between DA D1 receptors and NMDA conductance in the cortex.…”
mentioning
confidence: 65%